Respuesta :
Solution for 13-2n=19 equation:
Simplifying 13 + -2n = 19
Solving 13 + -2n = 19
Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right.
Add '-13' to each side of the equation. 13 + -13 + -2n = 19 + -13 Combine like terms: 13 + -13 = 0 0 + -2n = 19 + -13 -2n = 19 + -13
Combine like terms: 19 + -13 = 6 -2n = 6
Divide each side by '-2'. n = -3
Simplifying n = -3
Simplifying 13 + -2n = 19
Solving 13 + -2n = 19
Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right.
Add '-13' to each side of the equation. 13 + -13 + -2n = 19 + -13 Combine like terms: 13 + -13 = 0 0 + -2n = 19 + -13 -2n = 19 + -13
Combine like terms: 19 + -13 = 6 -2n = 6
Divide each side by '-2'. n = -3
Simplifying n = -3